Efficacy of Intravenous Cobinamide Versus Hydroxocobalamin or Saline for Treatment of Severe Hydrogen Sulfide Toxicity in a Swine (Sus scrofa) Model. (9th August 2017) - Bebarta, Vikhyat S.; Garrett, Normalynn; Brenner, Matthew; Mahon, Sari B; Maddry, Joseph K.; Boudreau, Susan; Castaneda, Maria; Boss, Gerry R.
Abstract: Background: Hydrogen sulfide (H2 S) is a potentially deadly gas that naturally occurs in petroleum and natural gas. The Occupational Health and Safety Administration cites H2 S as a leading cause of workplace gas inhalation deaths. Mass casualties of H2 S toxicity may be caused by exposure from industrial accidents or release from oil field sites. H2 S is also an attractive terrorism tool because of its high toxicity and ease with which it can be produced. Several potential antidotes have been proposed for hydrogen sulfide poisoning but none have been completely successful. Objective: The objective was to compare treatment response assessed by the time to spontaneous ventilation among groups of swine with acute H2 S‐induced apnea treated with intravenous (IV) cobinamide (4 mg/kg in 0.8 mL of 225 mmol/L solution), IV hydroxocobalamin (4 mg/kg in 5 mL of saline), or saline alone. Methods: Twenty‐four swine (45–55 kg) were anesthetized, intubated, and instrumented with continuous femoral and pulmonary artery pressure monitoring. After stabilization, anesthesia was adjusted such that animals would spontaneously ventilate with an FiO2 of 0.21. Sodium hydrosulfide (NaHS; concentration of 8 mg/mL) was begun at 1 mg/kg/min until apnea was confirmed for 20 seconds by capnography. This infusion rate was sustained for 1.5 minutes postapnea and then decreased to a maintenance rate for the remainder of the study to replicate sustained clinical exposure. Animals were randomly assigned to receive cobinamide (4 mg/kg), hydroxocobalamin (4 mg/kg), or saline and monitored for 60 minutes beginning 1 minute postapnea. G* power analysis using the Z‐test determined that equal group sizes of eight animals were needed to achieve a power of 80% in detecting a 50% difference in return to spontaneous ventilations at α = 0.05. Results: There were no significant differences in baseline variables. Moreover, there were no significant differences in the mg/kg dose of NaHS (5.6 mg/kg; p = 0.45) required to produce apnea. Whereas all of the cobinamide‐treated animals survived (8/8), none of the control (0/8) or hydroxocobalamin (0/8)‐treated animals survived. Mean (±SD) time to spontaneous ventilation in the cobinamide‐treated animals was 3.2 (±1.1) minutes. Conclusions: Cobinamide successfully rescued the severely NaHS‐poisoned swine from apnea in the absence of assisted ventilation.